Analysis Self-Management Ability Chronic Kidney Disease Patients With Hemodialysis (Journal of Namibian Studies : History Politics Culture, 2023)
Chronic kidney disease patients who undergo hemodialysis require good self-management skills due to the severity of their illness and the need for ongoing care. Hemodialysis can impact various aspects of a patient's life, including physiological, psychological, and socio-economic factors. Effective self-management is crucial in adapting to these changes, such as managing symptoms, medication, and lifestyle adjustments, as well as dealing with physical and psychosocial effects of the disease. Poor self-management ability is marked by patients' inability to control and manage these factors. Stress related to the disease and its treatment can also contribute to low self-management ability, as patients may struggle to use coping strategies. This study aimed to analyze the self-management ability of chronic kidney disease patients on hemodialysis using an analytic observational design with a cross-sectional approach. The sample included 105 respondents, and data collection involved a self-management questionnaire adapted from the Indonesian version of the Hemodialysis Self-Management Instrument (HDSMI). The results indicated that family support and health services were significantly related to self-management ability (p-values of 0.000 and 0.002, respectively), while physical symptoms and stressor assessment were not (p values of 0.694 and 0.499, respectively). Therefore, it can be concluded that family support and health services play an important role in enhancing self-management ability in chronic kidney disease patients undergoing hemodialysis.